Can you contribute even less? Specificity of rhetorical questions and their subtextual nature - Wowro, Iwona (Papers in Linguistics, 2023)
Rhetorical questions do not represent an independent type of questions and do not have a specific grammatical form but occur as a complex phenomenon with blurred boundaries that are set by the situational context. They violate the maxim of quality and do not fulfil the conditions for successful questioning since they have nothing in common with real questions except for their grammatical form. In the theoretical part of the article, their specificity and types are briefly presented, whereas the empirical part discusses their conventionalized structure and a few illocutionary indicators that point to rhetoricity as well as to the reinterpretation of the utterance.. The findings clearly show the ironic potential of rhetorical questions.